The development of problem sheets based on model eliciting activities learning to improve students’ mathematical communication ability - Lusiatri, Endah; Dewi, Nuriana Rachmani (Department of Mathematics, Universitas Negeri Semarang, 2020)
Problem Sheets are another form of the student worksheet that is arranged specifically in the Model Eliciting Activities (MEAs) learning. Students have to solve some problems in Problem Sheets with mathematical modeling. The purpose of this research was to produce a Problem Sheets based on MEAs learning which was guided by the indicators of students’ mathematical communication ability. This research is a type of Research and Development (R&D), the model used in this research is 4D Models consisting of 1) Define; 2) Design; 3) Develop; and 4) Disseminate. However, this research only went through three steps, they are 1) Define; 2) Design; and 3) Develop. The feasibility test result shows the Problem Sheets feasible is used in activities learning with a percentage of In addition, the readability test uses Cochran Test result shows that It means the students have the same understanding of the Problem Sheets given. After getting e-copyrights from the Directorate General of the Intellectual Property, the Problem Sheets based on MEAs learning is ready used for the next steps, that is testing in classroom learning.